FREQUENCY, RISK FACTORS, TREATMENT AND OUTCOMES OF HYPERINSULINEMIC HYPOGLYCEMIA IN NEONATES PRESENTING WITH PROLONGED HYPOGLYCEMIA IN A TERTIARY CARE HOSPITAL OF KARACHI, PAKISTAN - Vinod Kumar Hasija (Army Medical College Rawalpindi, 2020)
Objective: To identify frequency of hyperinsulinemic hypoglycemia in neonates with prolonged hypoglycemia, its risk factors, treatment and outcome.